2002
DOI: 10.1016/s1470-0328(02)01240-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell expression of adhesion molecules is induced by fetal plasma from pregnancies with umbilical placental vascular disease

Abstract: Objective To test the hypothesis that local production with spill into the fetal circulation of factor(s) injurious to endothelium is responsible for the vascular pathology present when the umbilical artery Doppler study is abnormal. Expression of adhesion molecules is a feature of endothelial cell activation. Design Case -control study.Setting University teaching hospital.Samples Fetal plasma was collected from 27 normal pregnancies, 39 pregnancies with umbilical placental vascular disease defined by abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
1
7
0
3
Order By: Relevance
“…Synthesis of proinflammatory cytokines IL‐6 and IL‐8 also occurred 13 . As further evidence these processes were occurring, we showed that fetal plasma from patients with an abnormal umbilical artery Doppler study contained increased levels of IL‐6 and IL‐8 14 and the soluble fractions of the adhesion molecules ICAM‐1 and PECAM‐1 11 . All of these findings pointed to injury of the vascular endothelium in the fetal umbilical placental circulation in cases with high resistance umbilical artery Doppler waveforms.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Synthesis of proinflammatory cytokines IL‐6 and IL‐8 also occurred 13 . As further evidence these processes were occurring, we showed that fetal plasma from patients with an abnormal umbilical artery Doppler study contained increased levels of IL‐6 and IL‐8 14 and the soluble fractions of the adhesion molecules ICAM‐1 and PECAM‐1 11 . All of these findings pointed to injury of the vascular endothelium in the fetal umbilical placental circulation in cases with high resistance umbilical artery Doppler waveforms.…”
Section: Introductionmentioning
confidence: 52%
“…There were no significant interactions between smoking, route of delivery and gestational age within the study groups for both iNOS and ecNOS expression. In this study, 65 patients were also included in our study of the endothelial cell adhesion molecule expression 11 . Two‐way analysis of variance showed no difference in the three study groups for the common and uncommon patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of proinflammatory cytokines IL-6 and IL-8 also occurred 13 . As further evidence these processes were occurring, we showed that fetal plasma from patients with an abnormal umbilical artery Doppler study contained increased levels of IL-6 and IL-8 14 and the soluble fractions of the adhesion molecules ICAM-1 and PECAM-1 11 . All of these findings pointed to injury of the vascular endothelium in the fetal umbilical placental circulation in cases with high resistance umbilical artery Doppler waveforms.…”
Section: Introductionmentioning
confidence: 73%
“…We also showed a factor in fetal plasma from these pregnancies, capable of inducing this change in endothelial cells in culture. 9,10 In this study, we sought to explore further the origin of the vascular pathology identified by the high-resistance umbilical artery Doppler flow velocity waveform. We hypothesised that injury to the endothelium in placental vascular disease would be evidenced by upregulation of the Egr-1 transcription factor.…”
Section: Introductionmentioning
confidence: 99%